German-USSR diplomatic cooperation in Baltic countries 1920–1940 - Butkus, Zenonas (Genocidas ir rezistencija, 2000)
German and USSR diplomats in the Baltic states cooperated closely during the inter–war period, maintaining much closer relations with each other than with envoys from other countries. These were not just the usual diplomatic contacts where opinions were exchanged, and issues of international life discussed. Diplomatic cooperation between the USSR and Germany was a specific policy, sanctioned and organised at the highest level of both countries. This policy was aimed at ensuring that the Baltic states, like the other countries between Germany and the USSR, would not form any alliance, that they would remain separate, isolated from each other, would not even have a coordinated foreign policy, in short, that no military–political bloc would emerge in Eastern and Central Europe that could in future hold back further expansion of Germany eastwards, and the USSR’s westwards.
Keywords: Soviet Union; Germany; Baltic countries; interwar period